Nitrogen to Potassium Ratios for Florida Golf Courses - Travis W. Shaddox; J. Bryan Unruh (EDIS)
Golf course nutrient management programs commonly include application of both nitrogen and potassium. These macronutrients are required by turfgrass in greater quantities than any other element except carbon, hydrogen, and oxygen. This 2-page fact sheet explains the Nitrogen to Potassium ratios that are best for golf courses. Written by T. W. Shaddox and J. B. Unruh, and published by the Environmental Horticulture Department, March 2017.